Examining the Variability in Planetary Boundary Layer Height over Thailand: Correlations with ENSO and Aerosol Optical Depth - Sirapong Sooktawee; Khwanruthai Renuhom; Siriwan Kaewket; Aduldech Patpai; Pramet Kaewmesri; Thongchai Kanabkaew; Pichnaree Lalitaporn (Applied Environmental Research)
Thailand has been facing air pollution, e.g., PM2.5, and impacts from climate phenomena, e.g., the El Niño‒Southern Oscillation (ENSO). Both air pollution and climate interact with each other. Changes in the planetary boundary layer height (PBLH) can affect PM2.5, represented by the aerosol optical depth (AOD), and are influenced by ENSO related to changes in the PBLH. The relationships among the PBLH, ENSO, and AOD were investigated via an empirical orthogonal function (EOF), which decomposes the spatiotemporal data of the PBLH into spatial patterns and corresponding time series. Correlation analysis was used to determine the relationships between the PBL variability time series and the ENSO and AOD variations in terms of interannual variability. The analysis focuses on December–February from 1991–2020 to identify dominant PBLH variability modes and their statistical relationships with ENSO and AOD. EOF analysis reveals three interesting principal components (DecPC2, JanPC3, and FebPC2) that account for 11.3–23.5% of the total PBLH variance and that exhibit spatial correlation patterns resembling ENSO-induced patterns. These modes show patterns that are consistent with the ENSO-driven influence on PBLH variations. However, the spatial correlations between the PBLH and AOD vary across Thailand. This finding indicates that AOD changes are not driven solely by ENSO. Some regions show strong PBLH-AOD correlations, whereas others exhibit weaker relationships. For example, the PBLH increases (decreases) over the northeastern region (west side) of Thailand, which is correlated with a reduction (increase) in AOD in February during the positive phase year. These findings highlight that the PBLH and ENSO alone do not fully determine the AOD changes in Thailand. Factors, such as fire emissions, monsoonal influences, and regional transport processes, play significant roles. Further studies are needed for a better understanding of the mechanism affecting air pollution to address the impacts of both air pollution and climate.